A Sporothrix spp. enolase derived multi-epitope vaccine confers protective response in BALB/c mice challenged with Sporothrix brasiliensis - Portuondo, Deivys Leandro [UNESP]; Batista-Duharte, Alexander [UNESP]; Cardenas, Constanza; Oliveira, Carlos S. de; Borges, Júlio César; Téllez-Martínez, Damiana [UNESP]; Santana, Paula Andrea; Gauna, Adriana; Mercado, Luis; Castilho, Bruna Mateus de [UNESP]; Costa, Paulo [UNESP]; Guzmán, Fanny; et al. (Elsevier, 2022)
Sporotrichosis is a cosmopolitan mycosis caused by pathogenic species of Sporothrix genus, that in Brazil is often acquired by zoonotic transmission involved infected cats with S. brasiliensis. Previous studies showed that the Sporothrix spp. recombinant enolase (rSsEno), a multifunctional protein with immunogenic properties, could be a promising target for vaccination against sporotrichosis in cats. Nevertheless, the considerable sequence identity (62%) of SsEno with its feline counterpart is a great concern. Here, we report the identification in silico, chemical synthesis and biological validation of six peptides of SsEno with low sequence identity to its cat orthologue. All synthesized peptides exhibit B-cell epitopes on the molecular surface of SsEno and proved to be highly reactive with the serum of infected mice with S. brasiliensis and sera of cats with sporotrichosis. Interestingly, our study revealed that anti-peptide sera did not react with the recombinant enolase from Felis catus (cats, rFcEno), thus, may not trigger autoimmune response in these felines if used as a vaccine antigen. The immunization with peptide mixture (PeptMix) formulated with Freund adjuvant (FA), induced high levels of antigen-specific IgG, IgG1 and IgG2b antibodies that conferred protection upon passive transference in infected BALB/c mice with S. brasiliensis. We also observed, that the FA+PeptMix formulation induced a Th1/Th2/Th17 cytokine profile ex vivo, associated with protecting effect against the experimental sporotrichosis. Our results suggest that the six SsEno-derived peptides here evaluated, could be used as safe antigens for the development of vaccine strategies against feline sporotrichosis, whether prophylactic or therapeutic.
Keywords: Enolase; Felis catus; Peptide vaccine; Sporothrix brasiliensis; Sporotrichosis